A dumbbell-like supramolecular triblock copolymer and its self-assembly of light-responsive vesicles1. Issue 59 (28th June 2015) - Zhang, Dapeng; Fan, Yujiao; Li, Huimei; Li, Ke; Yao, Yuan; Zhou, Yongfeng; Yan, Deyue
<x xml:space="preserve">Abstract</x> The work reports a dumbbell-like supramolecular triblock copolymer and its self-assembly of light-responsive monolayer vesicles.